A new species of Silba (Diptera; Lonchaeidae) associated with figs - Macgowan, Iain; Compton, Stephen G. (Zootaxa, 2018)
A new species of Silba Macquart 1851, Silba ischnopoda sp. nov., is described from Thailand and Cambodia. The Thailand individuals were obtained from larvae found in mature male figs of the dioecious Ficus ischnopoda Miq. Comparisons are made with other similar Asian Silba species which have also been reared from the figs of Ficus species. Male figs support development of fig wasp larvae, not seeds, suggesting that the larvae of S. ischnopoda may be predaceous.